Glosa do wyroku Trybunału Konstytucyjnego z dnia 22 września 2009 r., P 46/07 w sprawie zasadności zatrzymania prawa jazdy dłużnikowi alimentacyjnemu - Pietrzak, Helena (Prawo Kanoniczne, 2010)
Sejny Diocese was in the boarders of Warsaw Metropolis in the Congress Kingdom of Poland. The congregation hardly ever experienced presence of their priests, they rarely met them during priests` visits, neither were they preached in the form of pastorals. The Popes and bishops were the kind of people-symbols of unity of the whole Church and Diocese for their congregation. On the spot, in the parish, the parish priest was a real priest, landlord, and a registrar acting on behalf of the government. He, like other priests, took an oath of loyalty not only to the bishop, but also to the Tsar. The King-Emperor came from Orthodox Church. He himself and his surrounding lived convinced in superiority of secular authorities over the church ones, as it was according to eastern tradition. The government decided as regards the choice of the bishop, parish priest and other clergymen, setting up the parish and building churches. He also nationalized the parish land and calculated the priests` salaries, he wilfully closed down religious convents, issued regulations connected with staying of the priests at the place they worked in and wearing soutane. However, he did not enter the area of church doctrine. In churches people often prayed to God for the Tsar`s family, warmly welcomed their members when they were passing through. Orders regarding secular matters were announced from the pulpit. Looking back to the XIX the century lets us notice the difference in comparison to contemporary times.